Position statement on use of pharmacological combinations in a single pill for treatment of hypertension by Argentine Federation of Cardiology (FAC) and Argentine Society of Hypertension (SAHA) - Renna, Nicolás (2023)
The present document provides scientiﬁc evidence reviewed and analysed by a group of specialist clinicians in hypertension that aims to give an insight into a pharmacological strategy to improve blood pressure control. Evidence shows that most hypertensive patients will need at least two drugs to achieve blood pressure goals. There is ample evidence showing that treatment adherence is inversely related to the number of drugs taken. Observational studies show that use of drug combinations to initiate treatment reduces the time to reach the treatment goal and reduces CVD, especially with single pill combinations (SPCs). This work, based on recommendations of the Argentine Federation of Cardiology and Argentine Society of Hypertension as a reference, aims to review the more recent evidence on SPC, and to serve as guidelines for health professionals in their clinical practice and to the wider use of SPCs for the treatment of hypertension. Evidence from clinical trials on the effectiveness and adverse effects of using SPCs are provided. An analysis is also made of the main contributions of SPCs in special populations, e.g., elderly and diabetic patients, and its use in high risk and resistant hypertension. The effects of SPCs on hypertensive-mediated organ damage is also examined. Finally, we provide some aspects to consider when choosing treatments in the economic context of Latin-America for promoting the most efﬁcient use of resources in a scarce environment and to provide quality information to decision makers to formulate safe, cost-effective, and patient-centered health policies. Finally, future perspectives and limitations in clinical practice are also discussed.